PENERAPAN APLIKASI ANATES DALAM MENGANALISIS BUTIR SOAL PADA GURU MATA PELAJARAN EKONOMI SMA YAPI PADANG - stevani stevani; Vivina Eprillison; Dessyta Gumanti (XXXXX, 2022)
The position and high level of dedication of the teacher are essential to the effective delivery of instruction and learning in classrooms. The instructor must be able to perform their responsibilities and functions as a facilitator effectively. Teachers must be competent to facilitate learning, evaluate student work, employ learning media, and possess a thorough understanding of information and technology. The application of anates on instructors in the analysis of item items is one of the uses of learning media and assessment tools required by teachers. A computer application program called anates software seeks to examine individual things. Teachers believe that using Anates software is essential for assessing student learning outcomes, and observers of educational evaluation can also benefit from its use. However, because the teachers are unfamiliar with and do not comprehend how to utilize the Anates software, they still have trouble using the item analysis tool. This activity's objective is to give teachers useful practice in analyzing item questions using the anates application, particularly at YAPI Padang High School.